2015
DOI: 10.1681/asn.2014040328
|View full text |Cite
|
Sign up to set email alerts
|

Nephron Deficiency and Predisposition to Renal Injury in a Novel One-Kidney Genetic Model

Abstract: Some studies have reported up to 40% of patients born with a single kidney develop hypertension, proteinuria, and in some cases renal failure. The increased susceptibility to renal injury may be due, in part, to reduced nephron numbers. Notably, children who undergo nephrectomy or adults who serve as kidney donors exhibit little difference in renal function compared with persons who have two kidneys. However, the difference in risk between being born with a single kidney versus being born with two kidneys and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 63 publications
5
28
0
Order By: Relevance
“…Previous studies have linked larger nephrons to a higher single-nephron GFR in an animal model, 26 and the present study extends this finding to humans. In studies in animals, surgical renal ablation leads to a higher glomerular pressure and blood flow, which drives increases in both glomerular size and single-nephron GFR.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have linked larger nephrons to a higher single-nephron GFR in an animal model, 26 and the present study extends this finding to humans. In studies in animals, surgical renal ablation leads to a higher glomerular pressure and blood flow, which drives increases in both glomerular size and single-nephron GFR.…”
Section: Discussionsupporting
confidence: 82%
“…The apparent failure of the single-nephron GFR to increase with the expected age-related nephron loss, whereas it increased with nephro-sclerosis beyond the level expected for age, may support an age-based approach to the identification of chronic kidney disease. 25 Previous studies have linked larger nephrons to a higher single-nephron GFR in an animal model, 26 and the present study extends this finding to humans. In studies in animals, surgical renal ablation leads to a higher glomerular pressure and blood flow, which drives increases in both glomerular size and single-nephron GFR.…”
Section: Discussionsupporting
confidence: 80%
“…The link between low nephron number and the risk of hypertension and kidney disease has been shown in humans and experimental animals. 3436 Brenner et al 43 first identified an inverse association between nephron number and human hypertension. There has been great interest in the hypothesis proposed by this group that reductions in nephron numbers lead to glomerular hyperfiltration, enlargement, and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Azar et al 19 reported that kidneys of SS rats have 15% fewer nephron than age-matched salt-resistant rats. The loss of nephron has an inverse relationship with renal hemodynamics, BP, and renal function in human and rodent animal models, 3436 which is discussed later.…”
Section: Introductionmentioning
confidence: 99%